Antibody response after two doses of the BNT162b2 vaccine among healthcare workers of a Greek Covid 19 referral hospital: A prospective cohort study. Issue 5 (May 2022) - Tychala, Areti; Sidiropoulou, Eleni; Dionysopoulou, Sofia; Gkeka, Ioanna; Meletis, Georgios; Athanasiadis, Andreas; Boura-Theodorou, Anastasia; Chantzi, Chrysa; Koutri, Maria; Makedou, Kali; Skoura, Lemonia
Abstract: The global vaccination against SARS-CoV-2 has highlighted the need of assessing vaccines' immunogenicity against COVID-19. To evaluate humoral immunity induced by the BNT162b2 vaccine, we enrolled health care workers at AHEPA University Hospital of Thessaloniki, Greece to measure Anti-S SARS-CoV-2, anti-RBD SARS-CoV-2 and neutralizing antibodies. A total of 955 individuals with a median age of 50 years, were included in the study. Median values of antibodies were 1947.27 BAU/mL (Abbott SARS-CoV-2 IgG II Quant), 2064.98 BAU/mL (MAGLUMI SARS-CoV-2 S-RBD IgG) and 2464.63 IU/mL (MAGLUMI SARS-CoV-2 Neutralizing Antibodies). Individuals previously infected had greater antibody responses than infection naive ones and a 7-fold higher neutralizing antibodies titre. Antibodies degreased by age but not sex. Spearman's correlation coefficient among the three assays ranged from 0.903 to 0.969. The BNT162b2 vaccine was highly immunogenic in our cohort. Further research is needed to evaluate the vaccine's immunogenicity through time as well as in different populations. Abstract : BNT162b2; humoral immunity; Health care workers; SARS-CoV-2.